PENERAPAN STRATEGI PEMBELAJARAN AKTIF QUICK ON THE DRAW UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN LAJU REAKSI DI KELAS XI MIA SMA NEGERI 1 SIAK - Dian Rahayu Ningsih Rahayu Ningsih; R. Usman Rery Usman Rery; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Research on the application of strategy active learning Quick On TheDraw has been done to achieve student’s mastery learning on the subject of rate ofreaction in class XI MIA SMAN Siak.. Form of research is pra-experiment researchwith one-shot study case design. Data retrieval time from the date of 4 November to 20November 2014. The sample was selected from the three existing classes, namely classXI MIA 2. Data analysis technique used is to calculate presentation of classical masterylearning. Based on the final results of data processing using acquired mastery learningclassical is 90,91%, it’s means that the application of strategy active learning Quick OnThe Draw can achieve student’s mastery learning on the subject of rate of reaction inclass XI MIA SMAN 1 Siak.Keywords: Quick On The Draw, Mastery Learning, Rate of Reaction